АМУДАРЁ БЎЛИМИДА СУД–ҲУҚУҚ ТИЗИМИНИНГ ШАКЛЛАНИШИ - Абдуллаев, А. (SCIENCE and SOCIETY, 2024)
This article presents dato about the inclusion of the Amudarya region into the Russian Empire in the last quarter of the 19th century, we can see the issues of solving problems that may arise between the Russian population relocated to the country, as well as the local population and the Russians, and the process of the formation of the judicial system.
Keywords: court; law; Amudarya; empire; department; investigation; biy courts; Turkestan; governor-general; country; tribalism; military court; divisions